Measuring the Efficiency of Indonesian Insurance Companies Using Data Envelopment Analysis - Soewignyo, Fanny (JBE (Journal of Business and Economics); Volume 8 No.2, 2009 JBE UNKLAB, 2009)
The major aim of this research is to measure the relative efficiency of the six-selected Indonesia insurance companies listed in Indonesia Stock Exchange.  Data envelopment analysis (DEA) method was used to measure the relative efficiency of the insurance companies using the input-oriented CCR model, with constant returns to scale (CRS) assumption, developed by Charnes, Cooper and Rhodes and the input-oriented BBC model with variable returns to scale (VRS) as spefified by Banker, Charnes and Cooper. The results indicate that several insurance companies are in need of improvements in various areas.  DEA also points to the specific changes that must be made in the less productive insurance companies in order for them to catch up with their best practice peer group.